2017
DOI: 10.1111/nan.12428
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐associated microglia/macrophages predict poor prognosis in high‐grade gliomas and correlate with an aggressive tumour subtype

Abstract: (2018) Neuropathology and Applied Neurobiology 44, 185-206 Tumour-associated microglia/macrophages predict poor prognosis in high-grade gliomas and correlate with an aggressive tumour subtype Aims: Glioblastomas are highly aggressive and treatment resistant. Increasing evidence suggests that tumour-associated macrophages/microglia (TAMs) facilitate tumour progression by acquiring a M2-like phenotype. Our objective was to investigate the prognostic value of TAMs in gliomas using automated quantitative double i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(185 citation statements)
references
References 87 publications
(144 reference statements)
5
170
0
Order By: Relevance
“…They aggregate in and around glioma tissue and participate in the proliferation and invasion of tumour cells (Noy and Pollard, 2014;Wu and Watabe, 2017). There exists a positive correlation between the level of inflammatory cytokines inside the tumour micro-environment (TME) and the poor clinical prognosis of patients (Sorensen et al, 2018). Modulating the local inflammatory response has become a new strategy for immunotherapy due to its vital role in the development of tumours (Graf et al, 2002;Mineharu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They aggregate in and around glioma tissue and participate in the proliferation and invasion of tumour cells (Noy and Pollard, 2014;Wu and Watabe, 2017). There exists a positive correlation between the level of inflammatory cytokines inside the tumour micro-environment (TME) and the poor clinical prognosis of patients (Sorensen et al, 2018). Modulating the local inflammatory response has become a new strategy for immunotherapy due to its vital role in the development of tumours (Graf et al, 2002;Mineharu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The malignant phenotype of GB is supported by a favorable microenvironment which it orchestrates through an active secretome. Tumor‐associated macrophages and microglia (TAMs), which make up as much as 40% of the cellular content in GB, are recruited by chemoattractants that are produced by the tumor cell (Chen & Hambardzumyan, ; Hambardzumyan, Gutmann, & Kettenmann, ; Sorensen, Dahlrot, Boldt, Hansen, & Kristensen, ). TAMs are then induced by the tumor to produce soluble factors such as IL‐6, IL‐1, TGF‐β, and matrix metalloproteinases (MMPs) which enhance the motility, invasion, angiogenesis, and proliferation of both GB cells and glioma stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…induced to suppress anti-tumor immune cells through production of factors such as TGF-β and PD-L1 (Hambardzumyan et al, 2016;Noguchi et al, 2017;Sun, Mezzadra, & Schumacher, 2018). The positive influence of TAMs on GB progression is underscored by clinicopathological data associating higher tumor grade and worse prognosis with increasing populations of TAMs (Sorensen et al, 2018). The molecular response of TAMs to paracrine factors released by glioma cells is clearly complex and involves numerous signaling pathways and transcriptional factors such as STATs and NF-ĸB, (Holtman, Skola, & Glass, 2017;Li & Graeber, 2012).…”
mentioning
confidence: 99%
“…Male patients had more IBA1+ and CD204+ cells in their tumors based on the immunohistochemistry staining ( Fig. 5A), suggesting an increase in the immunosuppressive myeloid cell population 29 . Analysis of a separate cohort of male patients revealed that mMDSCs were the prevalent subset in human GBM tissue ( Fig.…”
Section: Male Patients Have An Enhancement In Tumor-infiltrating Mmdsmentioning
confidence: 96%
“…Specimens from 188 patients with a primary glioma diagnosis were stained with ionized calcium-binding adaptor molecule-1 (IBA-1) and cluster of differentiation 204 (CD204) 29 . The published dataset was reanalyzed by accounting for patient sex, and the IBA-1 and CD204 staining intensities were graphed separately for male versus female patients.…”
Section: Immunofluorescencementioning
confidence: 99%